Versuche zur Regulierung der Wühlmäuse im biologischen Obstbau - Kelderer, Markus; Lösch, Robert; Lardschneider, Ewald; Casera, Claudio (2000)
In the organic apple orchards in South Tyrol different voles (Fam. Arvicolidae) are the cause of big damages on the trees. At present there isn't any product listed t the annex 2b of the EC- decree 2092/91 for organic agriculture, which could control the voles efficiently. Therefore it is quite difficult to control the voles in organic orchards. It is necessary to convince European and national authorities, associations and organs of control to allow the use of suitable products. Our trials showed that Silmurin, an extract of the red sea-onion (Uriginea marsitima) controls quite efficiently the field mouse (Microtus arvalis), but hasn't any effect against the earth vole (Arvicola terrestris). Against these voles we obtained good results with Matox-cartridges based on sulphur gases. The results of the use of a machine which produces a mixture of CO and CO2 by burning organic materials were unsatisfactory with respect to both types of voles.